The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jhin.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Custom solution for personal protective equipment (PPE) in the orthopaedic setting: retrofitting Stryker Flyte T5 PPE system

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…A small number (15%) of respondents confirmed that they had used modified PPE due to either PPE shortages or in an attempt to reduce virus transmission during aerosol-generating orthopaedic procedures. The use of modified PPE for orthopaedic surgery and other surgical specialties has already been reported ( 31 , 32 , 33 , 34 , 35 ), and future research should be directed towards new developments and the study of their comparative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A small number (15%) of respondents confirmed that they had used modified PPE due to either PPE shortages or in an attempt to reduce virus transmission during aerosol-generating orthopaedic procedures. The use of modified PPE for orthopaedic surgery and other surgical specialties has already been reported ( 31 , 32 , 33 , 34 , 35 ), and future research should be directed towards new developments and the study of their comparative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, several modifications of surgical helmets have been suggested in the literature. [20][21][22][23] Nevertheless, many of these investigations utilize non-standardized testing procedures, making a direct comparison with the benchmark equipment difficult, if not impossible. Furthermore, most papers lack a complete characterization of the equipment considering the safety issues and the specific threats from bio-aerosols such as the SARS-CoV-19 virus.…”
Section: Previous Literaturementioning
confidence: 99%